2012
DOI: 10.1210/jc.2012-1894
|View full text |Cite
|
Sign up to set email alerts
|

Pigment epithelium-Derived Factor (PEDF) Varies with Body Composition and Insulin Resistance in Healthy Young People

Abstract: Context: Pigment epithelium-derived factor (PEDF) was recently implicated as a metabolic regulatory protein because plasma concentration was increased in obese or insulin resistant adults. To our knowledge, circulating PEDF values in children have not been reported. Because PEDF is a predictor of metabolic health in adults, it may have a similar impact on metabolic profiles in children.Objective: The objective of the study was to determine whether PEDF in normal-weight (NW) and overweight/obese (OW) children a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
3
13
0
Order By: Relevance
“…Our group recently reported that PEDF is increased in overweight/obese children compared with normal weight controls and positively associated in children with BMI and insulin resistance . Although PEDF was reported to be increased in adults with T2DM the non‐T2DM group in that study had significantly lower BMI so it was not clear whether the difference in PEDF was attributable to obesity or diabetes.…”
mentioning
confidence: 83%
“…Our group recently reported that PEDF is increased in overweight/obese children compared with normal weight controls and positively associated in children with BMI and insulin resistance . Although PEDF was reported to be increased in adults with T2DM the non‐T2DM group in that study had significantly lower BMI so it was not clear whether the difference in PEDF was attributable to obesity or diabetes.…”
mentioning
confidence: 83%
“…Circulating levels of C-reactive protein (CRP), lipids, SHBG, testosterone, high-molecular-weight (HMW) adiponectin and pigment epithelium-derived factor (PEDF) (only at 0, 18, and 24 months) (8) were measured together with safety assessments (blood count and circulating creatinine, aspartate aminotransferase, and alanine aminotransferase).…”
Section: Clinical and Endocrine-metabolic Assessmentsmentioning
confidence: 99%
“…Recently, PEDF has been defined as one of the most abundant adipokines, able to activate several signalling pathways, which in turn lead to insulin resistance (Borg et al, ). A few years ago, Sunderland et al () reported that plasma PEDF was elevated in overweight youth (Sunderland et al, ). In our study, PEDF mRNA was significantly up‐regulated by EPA only in visceral, but not in subcutaneous cells (Figure b).…”
Section: Discussionmentioning
confidence: 99%